Wildlife Smuggling in the Turkish Media - Kadriye Gizem Arıkan; Özgün Günen Buyuk; Bilge Yeni; Esra Per (Acta Infologica)
In terms of biodiversity, Turkey has the qualities of a small continent. Although it is not possible to legally trade the native species in the country (unless special permits are obtained), certain exotic and domestic species can be legally traded. For this reason, there are occasional cases of smuggling. There has been no assessment of bio-smuggling in the media across the country. In this study, news stories concerning smuggling were searched using different keywords in the Google search engine. These news items were analyzed in terms of the date, material type (fossil, bulb, seed, skin, nail, fur, horn, tooth, egg, poison, and individual), form (alive, dead), order, family, genus, species, geographical region, and province data. Of the news items analyzed, 45% were about bio-smuggling (native species), 44% exotic species, 7% farm animals and 2% pet smuggling. In the last ten years, there has been a remarkable increase in the trade of plant bulbs, teeth, skin, hides, shell and fur as opposed to live specimens. The Marmara Region was the source of 49% of the news items on smuggling. Within this region, Istanbul stands out in terms of the trade carried out through the airport, and Edirne with its land route trade. The history and current situation of news in Turkish media regarding the smuggling of wildlife species have been discovered as a result of this study. Of the news items analyzed, 37% were reported in 2020. The suspension of international wildlife trafficking due to the Covid 19 pandemic is thought to have an effect on this rate.